Effect of fertilizers type on production and fruits quality of Tomato in green house. - كناج, رزان (Latakia University Journal -Biological Sciences Series, 2021)
This study was carried out during 2018 Miaar Shaker village (Tartous) to determine the suitable type of fertilization on best production and fruits quality characters in plastic green-house. Two types of organic fertilizers were used in this study and treatment organic and of mineral fertilizers added to the control(without fertilizer). The results showed that chicken organic fertilizer gave better results in comparison with the other treatments in fruits indicators (plant productivity in treatment chicken manure (5.65 kg/plant).Tomato fruit from organic fertilizer gave better fruits quality as soluble solid matter, total sugar, acidity and vitamin C which is 28.72 mg vitamin C /100g in fresh matter. The fruit from treatment organic and of mineral fertilizers contain height rate of nitrate (11.37mg/kg) and nitrite(0.50 mg/kg).